Quality readiness and growth of Indian micro, small and medium enterprises. (1st January 2013) - Madan, Pankaj; Ghoshal, Moloy
With the increase in quality consciousness and expectations of the customers around the world, micro, small and medium enterprises (MSMEs) in India are also trying to keep up with the customers by improving the quality of their products. This paper is an assessment of quality readiness and growth of MSMEs of India. The focus of the study is to identify the quality readiness of these MSMEs on the scale of leadership, planning, infrastructure, people, resources and process management, customer and people satisfaction and to study the challenges associated with the quality of products and services. The study is conducted on export oriented leather, plastics and chemical industries of Uttar Pradesh, India. It also examines possible connections between enablers of quality deployment and quality readiness of MSMEs. Statistical analysis reveal, if there are any significant differences in the use and implementation of quality-related practices, across the low, moderate and high growth MSMEs. The outcomes may help other MSMEs on the pathway of quality improvement.